Sepsis Epidemiology and Outcomes in Pediatric Intensive Care Unit of Alkhadra Hospital, Tripoli, Libya - Fadelah Elghadban,; Sorour Abdulhakim, (AlQalam Journal of Medical and Applied Sciences, 2024)
Despite the various interventions and therapies that have been implemented to improve the quality of life for children with sepsis, the prevalence and death rates continue to increase. This issue is a major public health problem that requires the continuous improvement of the guidelines and the identification of new strategies. The aim of the study was to identify the prevalence and outcomes of severe sepsis among children admitted to the Pediatric Intensive Care Unit (PICU). This study was conducted in PICU of Alkhadra Hospital in 2023 as a hospital-based retrospective study. All children who were admitted to the PICU from 2017 to 2022 were included. Data was collected from hospital file records, which included the following: age of patient, gender, comorbidities of patients, and source of admission; origin of sepsis; type of PICU admission; primary site of infection; organ dysfunction present at screening; and patient outcomes. Of the 1284 total admissions to the PICU, 128 patients (9.96%) met the definition of sepsis. Most patients (78.9%) were less than 6 years old. Respiratory problems and congenital malformations were the most common co-morbidities, with reported rates of 18.8% and 10.2%, respectively. The emergency department was the most common source of admission (67.2%). Nearly all patients had good overall performance, whereas (21.1%) of the patients were in a coma. 77.3% discharged during the study, and 22.7% died. Although decreasing the incidence through preventive measures is ideal, early recognition and treatment of sepsis will decrease both short- and long-term complications and related mortality of at-risk infants and children. على الرغم من التدخلات والعلاجات المختلفة التي تم تنفيذها لتحسين نوعية حياة الأطفال المصابين بالتعفن، إلا أن معدلات الانتشار والوفيات تستمر في الارتفاع. هذه المشكلة هي مشكلة صحية عامة رئيسية تتطلب التحسين المستمر للمبادئ التوجيهية وتحديد استراتيجيات جديدة. كان الهدف من الدراسة هو تحديد انتشار ونتائج التعفن الشديد بين الأطفال الذين تم إدخالهم إلى وحدة العناية المركزة للأطفال. أجريت هذه الدراسة في وحدة العناية المركزة للأطفال في مستشفى الخضراء في عام 2023 كدراسة استرجاعية قائمة على المستشفى. تم تضمين جميع الأطفال الذين تم إدخالهم إلى وحدة العناية المركزة للأطفال من عام 2017 إلى عام 2022. تم جمع البيانات من سجلات ملفات المستشفى، والتي تضمنت ما يلي: عمر المريض والجنس والأمراض المصاحبة للمرضى ومصدر القبول؛ أصل التعفن؛ نوع القبول في وحدة العناية المركزة للأطفال؛ الموقع الأساسي للعدوى؛ خلل الأعضاء الموجود عند الفحص؛ ونتائج المرضى. من إجمالي 1284 حالة دخول إلى وحدة العناية المركزة للأطفال، استوفى 128 مريضًا (9.96%) تعريف التعفن. وكان معظم المرضى (78.9%) أقل من 6 سنوات. وكانت مشاكل الجهاز التنفسي والتشوهات الخلقية هي الأمراض المصاحبة الأكثر شيوعًا، حيث بلغت المعدلات المبلغ عنها 18.8% و10.2% على التوالي. وكان قسم الطوارئ هو المصدر الأكثر شيوعًا للقبول (67.2%). وكان أداء جميع المرضى تقريبًا جيدًا بشكل عام، في حين كان (21.1%) من المرضى في غيبوبة. وخرج 77.3% من المرضى أثناء الدراسة، وتوفي 22.7%. وعلى الرغم من أن تقليل حدوث التعفن من خلال التدابير الوقائية أمر مثالي، فإن التعرف المبكر على التعفن وعلاجه سيقلل من المضاعفات قصيرة وطويلة الأمد والوفيات المرتبطة به بين الرضع والأطفال المعرضين للخطر